حدیث معمول بہ کی تعیین میں سبب ورود کا کردار: The Role of Context of Revelation in Determining Practiced Hadith - Muhammad Akhlaq; Muhammad Owais Alkhari (International Research Journal of Arabic and Islamic Studies, 2023)
The context of revelation, known as "Asbab al-Warood" in Arabic, plays a significant role in understanding and determining the classification of hadith, including identifying those that are considered moderate. Here's how it factors in Clarifying, Meaning and Intent, Understanding the specific circumstances under which a hadith was revealed or spoken helps clarify its meaning and intent. This context can determine whether a hadith is prescriptive for all times or specific to a particular situation. Avoiding Misinterpretation, Knowing the context helps avoid taking hadith out of context, which can lead to misinterpretation and extreme views. This is crucial for ensuring that the hadith is applied appropriately and moderately. Determining Abrogation, Some hadiths may appear contradictory. Understanding the context can help scholars determine if a particular hadith abrogates another, thereby identifying which hadith is to be followed in a given situation. Applying Principles of Fiqh, Contextual knowledge allows scholars to apply principles of Islamic jurisprudence (Fiqh) correctly. This helps in deriving moderate rulings that are in line with the spirit of Islam. Evaluating Authenticity, Contextual information can also assist in evaluating the authenticity of a hadith. If the context is well-documented and aligns with other known historical facts, it supports the hadith's reliability. By thoroughly understanding the context of revelation, scholars can ensure that the interpretation and application of hadith remain balanced, avoiding extremes and aligning with the overall objectives of Sharia (Maqasid al-Sharia).